A holistic, user-driven approach to the development of an innovative, open-access Educational Framework for six existing and emerging information-related literacies - Foteini, Efthymiou; Kouis, Dimitris (Journal of Integrated Information Management, 2019)
Purpose - This article discusses a holistic, user-driven approach for the development of an innovative, open-access Educational Framework that includes six emerging information-related literacies. The Educational Framework of these literacies should be based on the structural support offered by the various Information Literacy models and is addressed to educators and librarians. Design/methodology/approach The proposed Educational Frameworks’ possible stakeholders and partners should plan for specific activities that will lead to the achievement of three main objectives: (a) the development of a freely available Information Literacy Training Package; (b) the training of educators and librarians, in the core skills of Information Literacy, as a horizontal goal and in new literacies as vertical goals; (c) the convergence in terms of strategy, expertise and infrastructure in Information Literacy initiatives, at a co-operative and even at a transnational level. Expected impact – The open access dissemination of information-related literacies concerning: critical thinking regarding issues of equality and tackling the social injustices against marginalized groups in communities; making the most of peoples’ multiple interactions with digital technology and media; mobile tailored learning contents are cost effective and accessible for persons with learning disabilities; freedom of expression and information, empowerment of citizens to understand the functions of media and other information providers, to critically evaluate their content, and to make informed decisions as users and producers of information and media content; understanding and production of reliable news stories and scientific papers, based on data; dissemination and fostering of the Sustainable development goals, through the lenses of Information Literacy. Originality/value - The proposed Educational Framework is a conceptually, strategically, technologically and educationally pioneering endeavor in answering specific urgent demands of the current Information and Knowledge Society.